Proteomic profile of carbonylated proteins in rat liver: Exercise attenuated oxidative stress may be involved in fatty liver improvement. Issue 10 (2nd May 2013) - Hu, Xiaofei; Duan, Zhigui; Hu, Hui; Li, Guolin; Yan, Siyu; Wu, Jinfeng; Wang, Jun; Yin, Dazhong; Xie, Qingji
Abstract : To screen target proteins of oxidative stress which mediate the effects of exercise on preventing nonalcoholic fatty liver disease (NAFLD), the methods for selecting carbonylated proteins were modified, and carbonylated proteins were profiled. The results showed that treadmill training reduced oxidative stress and the levels of intrahepatic triglyceride (IHTG). The changes in IHTG showed a significant positive correlation with oxidative stress as indicated by malondialdehyde level. Further results from proteomics illustrated that 17 functional proteins were susceptible to oxidative modification, and exercise protected three proteins from carbonylation. The latter three proteins may serve as both direct target proteins of oxidative stress and mediators contributing to the beneficial effects of exercise. In particular, a long‐chain specific acyl‐CoA dehydrogenase (ACADL) which was a key enzyme in lipid metabolism was not carbonylated and with higher activities in exercise group. These findings indicate that this modified technique is practical and powerful in selecting carbonylated proteins. Long‐term treadmill training is effective in ameliorating oxidative stress and preventing the accumulation of IHTG. Among the 17 target proteins of oxidative modification, three proteins contribute to the beneficial effects of exercise. Preventing ACADL from carbonylation may be involved in the physiological mechanism of exercise‐induced NAFLD improvement.